Changes in erythrocyte methylmercury among women during pregnancy: a monocentric survey and comparison study - Xing CHEN; Jia-yao LUO; Huan CHEN; Xi CHEN (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To investigate changes in peripheral erythrocyte methylmercury among pregnant women during different gestational periods and the methylmercury in neonatal umbilical cord blood erythrocyte. MethodsTotally 79 pregnant women having prenatal examination were recruited at a women's and children's health care center in Wuhan city during January - April, 2019. The women's peripheral blood samples were collected at the first trimester (12 ± 2 weeks of gestation) and the third trimester (37 ± 2 weeks of gestation) and neonatal umbilical cord blood samples were also collected. Red blood cells of the samples were separated and concentrations of methylmercury in the cells were detected with high performance liquid chromatography-inductively coupled plasma mass spectrometry (HPLC-ICP-MS). Results The geometric means of erythrocyte methylmercury of all the women were 0.322 μg/g (interquartile range [IRQ]: 0.188 - 0.728 μg/g) for the samples of first trimester, 0.238 μg/g (IRQ: 0.120 - 0.549 μg/g ) for those of third trimester, and 0.515 μg/g (IRQ: 0.322 - 1.099 μg/g) for neonatal umbilical cord samples. The erythrocyte methylmercury of the first trimester samples was significantly higher than that of the third trimester samples (P < 0.05); while, the erythrocyte methylmercury of both the first trimester and the third trimester samples were significantly lower than that of neonatal umbilical cord samples (both P < 0.05). The erythrocyte methylmercury of the umbilical cord blood samples, the first trimester samples and the third trimester samples were closely correlated with each other, with the correlation coefficients of 0.763, 0.866, and 0.854, respectively. Conclusion The erythrocyte methylmercury of pregnant women during first and third trimester and that of neonatal umbilical cord blood are significantly correlated with each other. Higher erythrocyte methylmercury of neonatal umbilical cord blood than that of women during pregnancy suggests a possible enrichment of methyl mercury.